Conditions for Pedestrian Traffic in Costa Rica - Sánchez, Adriana (2010)
It seeks to understand the causes that produce and reproduce violence and situations of risk while traveling through the country roads.Ranked pedestrian traffic conditions in Costa Rica based on three elements that is determined to contribute to enhance the risk for these types of users: policy, the infrastructure and socio-geographic.